Bipartite Role of Heat Shock Protein 90 (Hsp90) Keeps CRAF Kinase Poised for Activation - Mitra, Shahana (J Biol Chem, 2016)
CRAF kinase maintains cell viability, growth, and proliferation by participating in the MAPK pathway. Unlike BRAF, CRAF requires continuous chaperoning by Hsp90 to retain MAPK signaling. However, the reason behind the continuous association of Hsp90 with CRAF is still elusive. In this study, we have identified the bipartite role of Hsp90 in chaperoning CRAF kinase. Hsp90 facilitates Ser-621 phosphorylation of CRAF and prevents the kinase from degradation. Co-chaperone Cdc37 assists in this phosphorylation event. However, after folding, the stability of the kinase becomes insensitive to Hsp90 inhibition, although the physical association between Hsp90 and CRAF remains intact. We observed that overexpression of Hsp90 stimulates MAPK signaling by activating CRAF. The interaction between Hsp90 and CRAF is substantially increased under an elevated level of cellular Hsp90 and in the presence of either active Ras (Ras(V12)) or EGF. Surprisingly, enhanced binding of Hsp90 to CRAF occurs prior to the Ras-CRAF association and facilitates actin recruitment to CRAF for efficient Ras-CRAF interaction, which is independent of the ATPase activity of Hsp90. However, monomeric CRAF (CRAF(R401H)) shows abrogated interaction with both Hsp90 and actin, thereby affecting Hsp90-dependent CRAF activation. This finding suggests that stringent assemblage of Hsp90 keeps CRAF kinase equipped for participating in the MAPK pathway. Thus, the role of Hsp90 in CRAF maturation and activation acts as a limiting factor to maintain the function of a strong client like CRAF kinase.